The Unusual Morphology, Structure, and Magnetic Property Evolution of Glassy Carbon upon High Pressure Treatment - C.Q. Jin (Brazilian Journal of Physics, 2003)
Glassy carbon (GC) has been high-pressure high-temperature treated. An interesting morphology evolution from the pristine sample to the high pressure products was observed. It is found that GC can be graphitized under pressure at a temperature much lower than that at ambient condition. Furthermore the in¡situ structure and electrical measurements of GC and graphitized glassy carbon (GGC) under high temperature and high pressure have been investigated up to 30 GPa. We particularly emphasize the unusual magnetic properties of GC treated under high pressures and high temperatures. A paramagnetic to ferromagnetic-like, and then to superconducting (a diamagnetic signal with hysteresis magnetic response) -like behavior, which can be observed at temperatures as high as 80 K, appears as a successive evolution from the initial GC to GGC in accordance with three regions distinguished by the graphitization temperature. This interesting evolution of magnetic properties probably evokes the new understanding of carbon element.